« Par Irène Némirovsky, pour Irène Némirovsky » : les jeux de miroir du biographique - Elena Quaglia (Revue Italienne d'Etudes Françaises, 2023)
This article analyses the writing of the novel Le Vin de solitude, the autobiographical dimension of which is highlighted by the process of transposition used by the author, from the drafts to the final text. A study of Némirovsky’s work diaries, held by the IMEC, sheds light on the biographical aspects of the novel. The pre-text, the text and the intertexts thus form a highly complex network through which the novelist explores the difficulties of a childhood deprived of maternal love.